O empreendedorismo como um processo: um estudo de casos múltiplos - Peixoto Filho, Heitor Penteado de Mello (2009)
This study is focused on the opportunity or voluntary entrepreneurship, the one resulting from the identification of a good business opportunity. The premise is that entrepreneurship is a process with five main phases, going from the recognition of a good business opportunity until the harvest of rewards, with the exit of the founders. Each one of these phases was researched based on the trajectory of three entrepreneurs and their respective companies, with the objective of detailing the main internal and external factors to the constitution and development of the companies, the main strategic decisions taken by the entrepreneurs in function of these factors, the main adopted strategies and their process of formulation, always in the search of standards. This is an exploratory research. The study of incorporated multiple cases was opted as the procedure for data collection. The primary unit of analysis was the entrepreneur, three in total, all of them idealizers, partners and main managers of their respective companies. Focused interviews were conducted, with a script composed of forty four items. The study suggests that the entrepreneurship can in fact be considered as a process, with five main stages, each one with relatively well delimited and proper characteristics. Some standards had been identified in the entrepreneur s profile, standing out their good academic background. Regarding the companies' profile, it was observed that all of them were medium-sized and lucrative at the date of the selling. In relation to the entrepreneurial process, all companies had a modest start-up and with few investments. Finally, they all adopted a common set of strategies, which included innovation, concentration in only one business and partnerships